2004
DOI: 10.1038/ni1146
|View full text |Cite
|
Sign up to set email alerts
|

Lethal anemia caused by interferon-β produced in mouse embryos carrying undigested DNA

Abstract: The livers of DNase II-deficient mouse embryos contain many macrophages carrying undigested DNA, and the embryos die in utero. Here we report that erythroid precursor cells underwent apoptosis in the livers of DNase II-deficient embryos and that in the liver, interferon-beta mRNA was expressed by the resident macrophages. When the DNase II-deficient mice were crossed with mice deficient in type I interferon receptor, the resultant 'double-mutant' mice were born healthy. The double-mutant embryos expressed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
281
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(295 citation statements)
references
References 41 publications
9
281
1
Order By: Relevance
“…Mice lacking DNase II show a dramatic STING-dependent type I IFN response because of the fact that DNA within the lysosomal compartment of phagocytic cells fails to be degraded and subsequently translocates into the cytoplasm (23). It appears likely that cGAS also plays a pivotal role in this disease setting, yet additional proof is required to substantiate this assumption.…”
Section: Discussionmentioning
confidence: 98%
“…Mice lacking DNase II show a dramatic STING-dependent type I IFN response because of the fact that DNA within the lysosomal compartment of phagocytic cells fails to be degraded and subsequently translocates into the cytoplasm (23). It appears likely that cGAS also plays a pivotal role in this disease setting, yet additional proof is required to substantiate this assumption.…”
Section: Discussionmentioning
confidence: 98%
“…Although an increase in antimicrobial peptide production would be expected to partially compensate for the loss of hemocyte function, this was clearly not the case. This perplexing result is reminiscent of the embryonic lethality observed in dnase II-knockout mice which is caused by an unexpected overexpression of INF-β by macrophages [10][11][12]. Apart from antimicrobial peptide induction, it has been demonstrated that dDNase II itself is significantly induced by bacterial and fungal infection [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, targeted mutation of the dnase II gene in the germline of mice resulted in perinatal lethality presumably due to loss definitive erythropoiesis [9,10]. Subsequent analyses of these mutant mice revealed that dnase II-deficient macrophages accumulate ingested DNA and overexpress β-interferon (INFβ) resulting in embryonic lethality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions, self DNA is inappropriately delivered to the cytosol, resulting in autoimmune responses. For example, DNase II-deficient macrophages lack the ability to digest self-DNA from engulfed apoptotic cells, leading to IFN-β production Yoshida et al, 2005). However, the mechanism by which cytosolic DNA induces IFNs is not well understood.…”
Section: Introductionmentioning
confidence: 99%